Role of Finance in Economic Growth in India: An Emperical Analysis - Mishra, Parul (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
This paper uses quarterly data from 1991 to 20015 to examine the impact of financial development on economic growth in India during the post-reform reform period. This study used ADF and PP tests to identify quiescent states between variables. Since most financial variables are inherently volatile, if the study performs a regression analysis directly on highly volatile data, the results may be suspicious and unexpected. Therefore, the study conducted a fixed test and found that financial development, i.e., M3 / GDP and growth rate is integrated at the level of 5%, to the level of significant I (1). Second, Johnsoen and Jesulisu (1991) were used to find long-term relationship cointegration vectors. The sign of the M3 / GDP coefficient is positive to previous expectations. India has a positive impact on financial development. Demonstrates that financial development plays an important role in India's economic growth. Integral relations support the existence of long-term equilibrium relationships between variables in the context of India. It also reports on Granger causality, supporting the findings supporting India's financial-driven growth hypothesis. The study concludes that financial development is more conducive to long-term growth and in the long run is not the opposite as one of the determinants of economic growth. Increasing money market interest rates have a positive impact on economic growth. Keywords: financial development, reform, economic growth, co-integration, causality.